Immune checkpoint inhibitors in MITF family translocation renal cell carcinomas and genetic correlates of exceptional responders. Issue 1 (27th December 2018) - Boilève, A.; Carlo, M. I.; Barthélémy, P.; Oudard, S.; Borchiellini, D.; Voss, M. H.; George, S.; Chevreau, C.; Landman-Parker, J.; Tabone, M-D; Chism, D. D.; Amin, A.; et al.
Abstract : Background: Microphthalmia Transcription Factor ( MITF )family translocation renal cell carcinoma (tRCC) is a rare RCC subtype harboring TFE3 / TFEB translocations. The prognosis in the metastatic (m) setting is poor. Programmed death ligand-1 expression was reported in 90% of cases, prompting us to analyze the benefit of immune checkpoint inhibitors (ICI) in this population. Patients and methods: This multicenter retrospective study identified patients with MITF family mtRCC who had received an ICI in any of 12 referral centers in France or the USA. Response rate according to RECIST criteria, progression-free survival (PFS), and overall survival (OS) were analyzed. Genomic alterations associated with response were determined for 8 patients. Results: Overall, 24 patients with metastatic disease who received an ICI as second or later line of treatment were identified. Nineteen (82.6%) of these patients had received a VEGFR inhibitor as first-line treatment, with a median PFS of 3 months (range, 1–22 months). The median PFS for patients during first ICI treatment was 2.5 months (range, 1–40 months); 4 patients experienced partial response (16, 7%) and 3 (12, 5%) had stable disease. Of the patients whose genomic alterations were analyzed, two patients with mutations in bromodomain-containing genes ( PBRM1 and BRD8 ) had a clinical benefit. Resistant clones in a patient with exceptional response to ipilimumab showed loss of BRD8 mutations and increased mutational load driven by parallel evolution affecting 17 genes (median mutations per gene, 3), which were enriched mainly for O-glycan processing (29.4%, FDR = 9.7 × 10 − 6 ). Conclusions: MITF family tRCC is an aggressive disease with similar responses to ICIs as clear-cell RCC. Mutations in bromodomain-containing genes might be associated with clinical benefit. The unexpected observation about parallel evolution of genes involved in O-glycosylation as a mechanism of resistance to ICI warrants exploration.